2019
DOI: 10.3390/md17120659
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cell Detachment Ratio of Mesenchymal-Type Lung Cancer Cells on pH-Responsive Chitosan through the β3 Integrin

Abstract: Chitosan is sensitive to environmental pH values due to its electric property. This study investigates whether the pH-responsive chitosan assay can provide a simple method to evaluate the aggressive behavior of cancer cells with cell detachment ratio. The epithelial–mesenchymal transition (EMT) is induced with transforming growth factor-β1 (TGF-β1) in the human non-small cell lung cancer cell line (A549). EMT-induced cells and untreated cells are cultured on chitosan substrates at pH 6.99 for 24 h, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For the achievement of continuous cell production, the prepared PA/CS blends were examined using the modified cell detachment assay developed in the previous study [ 29 ], as illustrated in Fig. 3 A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the achievement of continuous cell production, the prepared PA/CS blends were examined using the modified cell detachment assay developed in the previous study [ 29 ], as illustrated in Fig. 3 A.…”
Section: Resultsmentioning
confidence: 99%
“…Cell numbers of the detached and the remaining adherent cells on the blended substrates were determined by CyQUANT assay kit (C35006; Invitrogen, Thermo Fisher Scientific) according to the manufacturer's instructions. Cell detachment ratio was calculated as the previous reported method [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…EMT is a developmental process that promotes the transition of epithelial cells to migratory mesenchymal cells (27). Previous articles have reported that EMT is involved in the occurrence, development, and metastasis of tumors, in which it plays an important role (28,29), with a great correlation with cancer metastasis (30). Due to the different driving factors of EMT in different tumor types or in different stages of the occurrence and development of the same tumor, its role in tumor metastasis is not the same (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%